SEBUAH KARYA FEATURE WISATA DAN PERJALANAN “TABLE STORY” - Rangga Sikunantindi; Muhammad Darwinsyah (Inter Community: Journal of Communication Empowerment, 2019)
Current feature programs broadcast on Indonesian television have begun to be of little interest to the public, because they have begun to be displaced by other television programs whose content is merely entertainment. Though the community needs various programs that are able to provide information, inspiration and education in order to provide and increase awareness of the potential of their own people. The creator of the work wants to create a program that has a lot of information, inspiration and education about culinary from both the dish and the place. This program is a culinary travel feature titled "TABLE STORY", a program that packages a variety of unique culinary found in Indonesia, this program not only discusses my food but also provides in-depth information about the theme of the food and the place itself which has the desires to be the hallmark of the place itself and also a place that provides education for its customers. This program has a total duration of 15 minutes. This program will be aired once a week on Saturdays at 09.30 WIB, on the private television station SCTV (Surya Citra Televisi). The creator of the work has consideration of choosing the time and placing this program on the SCTV television station, because the television station does not have a culinary program that discusses in depth the presentation and design of the culinary place, so that this program can provide information, inspiration, and education to audience at the station.